PENGARUH ADVERTISING DAN SALES PROMOTION TERHADAP KEPUTUSAN PEMBELIAN PRODUK GALON 19 LITER AIR MINUM DALAM KEMASAN (AMDK) PT SEGAR MURNI UTAMA DI KOTA MOJOKERTO - Muhammad Triantono; Achmad Zaini (CV. ADIBA AISHA AMIRA, 2024)
Every company always tries to develop its business in order to maintain the continuity of the company's marketing. Various ways need to be taken to maintain this by arranging planning and implementing the use of marketing strategies in the form of advertising and sales promotion. One company that utilizes advertising and sales promotion is PT Segar Murni Utama (Mojo Tras). So kolthis study aims to analyze the effect of advertising and sales promotion on purchasing decisions of 19L Mojo Tras gallon water products. This type of research uses descriptive statistics, with a quantitative approach. The sample used was 60 respondents, using the Stratification Random Sampling approach. The instrument used in the study used a questionnaire with a Likert scale using multiple linear regression analysis as the data analysis method. The results of the hypothesis show that partially Advertising has a positive and significant effect on purchasing decisions of 19-liter gallon Mojo Tras products and Sales Promotion also has a positive and significant effect on purchasing decisions of 19-liter gallon Mojo Tras products. Meanwhile, simultaneously advertising and sales promotion have a positive and significant effect on purchasing decisions for 19-liter gallon Mojo Tras products. From the results of this study, it can be concluded that advertising and sales promotion can influence purchasing decisions on 19-liter gallon Mojo Tras products. It is hoped that Mojo Tras will be more selective in choosing advertising and can improve the quality of advertising on its Instagram platform and be more active in making offers to benefit consumers